EVALUASI JALUR EVAKUASI BENCANA GUNUNG API SEULAWAH AGAM DI KECAMATAN SEULIMUM KABUPATEN ACEH BESAR - T. Saiful Bahri; Mirza Irwansyah; Didik Sugianto (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
This thesis discusses the evaluation of evacuation route of the volcanic disaster of Seulawah Agam in Seulimum sub-district of the District of Aceh Besar. Evacuation route is a special path that links all affected areas to a safer area (Gathering Point). The evacuation route and evacuation point are determined in a participatory way so that it can reduce the vulnerability level of the community. Qualitative method is used in this research. Source of data that used in this research consists of primary data (field research) and secondary data (library research). The results of analyzing the data show that the condition of the village main road as the community evacuation route established very well, however certain areas need several improvements such as street lighting need to be added especially at the crossroads, and disaster evacuation signs have not yet been installed, making it more difficult for the residents during the evacuation process. All residents in the three villages 100% stated that the community involvement in the planning of evacuation route is very important in order to achieve the result that suitable to the needs of the community and the environmental condition. In general, the level of community involvement in the evacuation route planning process has been very well. The community actively participated during the process. Around 50% of the residents Gampong Iboih Tanjong actively and excellently involved during the process, for the community involvement  55% of residents of Gampong Iboih Tunong actively and excellently involved during the planning process, the third village, Gampong Alue Rindang, 65% of residents of Gampong Iboih Tunong actively and excellently involved during the planning process. With the high level of community involvement during the evacuation planning process, it is expected the evacuation route that has been made before will be able to quickly and efficiently help the community in evacuation process once the disaster occurred